What Intellectual Property Law Should Learn from Software. - BOYLE, JAMES (Communications of the ACM, 2009)
The article refers to intellectual property law in the United States and focuses on the computer industry where software is protected by patent and copyright. The issues of a network effect impacting innovation in software development, of the outlook for using intellectual property rights to protect software, of the "commons-based creativity" argument for allowing access to open source software, of a perception that the U.S. court system's view of computers is related to unpatentable ideas and multiple patentable machines, and of the rationale for wanting to patent business methods.